The role of MTHFR polymorphism on hyperhomocysteinemia and folic acid and vitamin B metabolism - Triana, Rina (Indonesian Nutrition Association, 2025)
Non-communicable diseases (NCDs) remain a leading global health concern, with hyperhomocysteinemia recognized as a contributing metabolic disorder linked to cardiovascular disease, neurodegenerative conditions, and developmental anomalies. This presentation explores the pivotal role of methylenetetrahydrofolate reductase (MTHFR) polymorphisms—particularly C677T and A1298C variants—in disrupting homocysteine metabolism through impaired folate and vitamin B pathways.